Improving Predictions of High‐Latitude Coronal Mass Ejections Throughout the Heliosphere. Issue 3 (2nd March 2020) - Scolini, C.; Chané, E.; Pomoell, J.; Rodriguez, L.; Poedts, S.
Abstract: Predictions of the impact of coronal mass ejections (CMEs) in the heliosphere mostly rely on cone CME models, whose performances are optimized for locations in the ecliptic plane and at 1 AU (e.g., at Earth). Progresses in the exploration of the inner heliosphere, however, advocate the need to assess their performances at both higher latitudes and smaller heliocentric distances. In this work, we perform 3‐D magnetohydrodynamics simulations of artificial cone CMEs using the EUropean Heliospheric FORecasting Information Asset (EUHFORIA), investigating the performances of cone models in the case of CMEs launched at high latitudes. We compare results obtained initializing CMEs using a commonly applied approximated (Euclidean) distance relation and using a proper (great circle) distance relation. Results show that initializing high‐latitude CMEs using the Euclidean approximation results in a teardrop‐shaped CME cross section at the model inner boundary that fails in reproducing the initial shape of high‐latitude cone CMEs as a circular cross section. Modeling errors arising from the use of an inappropriate distance relation at the inner boundary eventually propagate to the heliospheric domain. Errors are most prominent in simulations of high‐latitude CMEs and at the location of spacecraft at high latitudes and/or small distances from the Sun, with locations impacted by the CME flanks being the most error sensitive. This work shows that the low‐latitude approximations commonly employed in cone models, if not corrected, may significantly affect CME predictions at various locations compatible with the orbit of space missions such as Parker Solar Probe, Ulysses, and Solar Orbiter. Key Points: We use the EUHFORIA heliospheric model to investigate the modeling of high‐latitude cone CMEs We find that commonly used low‐latitude approximations fail in reproducing the initial shape of high‐latitude cone CMEs If not corrected, such approximations may affect predictions at locations of high latitude and close‐to‐the‐Sun space missions